Evaluation of Economic and Social Parameters of Smart City Growth Impact (Case Study: Isfahan City) - sajedeh karimi (تحقیقات کاربردی علوم جغرافیایی)
Many efforts have been made to address the negative effects of sprawling urban expansion, which can be referred to as "smart growth" as a strategy for urban sustainability. The purpose of this study was to evaluate the impact of smart city growth on economic and social parameters in Isfahan. The present study is descriptive-analytical in terms of the type of research and is applied-developmental in terms of purpose. The statistical population of the study consisted of the population of Isfahan city in the Census of 2016 (5120850). The research tool was a researcher-made questionnaire (Smart City Questionnaire, Economic Questionnaire and Social Questionnaire) with 32 questions. The validity of the questionnaire was formal, which was confirmed by experts and professors, and its reliability by Cronbach's alpha was 0.84. Data analysis, based on structural equation analysis, was performed in AMOS software. The results indicate that urban smart growth in Isfahan is influenced by social and economic variables, among which the role of economic variables in urban smart growth have more influence than social variables, which impact factor of economic variable role. It was 0.71, while the social variable had an impact factor of 0.38.